2021
DOI: 10.3389/fonc.2021.697894
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Glucose or Glutamine Metabolic Therapy Combined With PD-1/PD-L1 Checkpoint Blockade Immunotherapy for the Treatment of Tumors - Mechanisms and Strategies

Abstract: Immunotherapy, especially PD-1/PD-L1 checkpoint blockade immunotherapy, has led tumor therapy into a new era. However, the vast majority of patients do not benefit from immunotherapy. One possible reason for this lack of response is that the association between tumors, immune cells and metabolic reprogramming in the tumor microenvironment affect tumor immune escape. Generally, the limited amount of metabolites in the tumor microenvironment leads to nutritional competition between tumors and immune cells. Metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 91 publications
0
17
0
Order By: Relevance
“…In addition, the high expression of the GLNM regulators was significantly positively correlated with PD-L1 expression, as was the case in previous studies. Previous studies have demonstrated that the expression of PD-L1 was upregulated in renal cancer cells in glutamine deprivation culture medium via the EGFR/ERK/C-Jun pathway [ 41 ]. The expression of PD-L1 was mediated via the nuclear factor-kappa B (NF-kB) signaling pathway, which was activated by the reduction in GSH levels [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the high expression of the GLNM regulators was significantly positively correlated with PD-L1 expression, as was the case in previous studies. Previous studies have demonstrated that the expression of PD-L1 was upregulated in renal cancer cells in glutamine deprivation culture medium via the EGFR/ERK/C-Jun pathway [ 41 ]. The expression of PD-L1 was mediated via the nuclear factor-kappa B (NF-kB) signaling pathway, which was activated by the reduction in GSH levels [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the metabolic interaction between tumor cells and immune cells may be related to poor response to immunotherapy. Therefore, targeting tumor metabolic activity including glucose or glutamine activity combined with PD-1/PD-L1 ICIs may provide new treatment opportunities for gastric cancer patients ( Ma et al, 2021 ). We analyzed the co-expression relationship between 14 metabolic genes and PD-1/CTLA4 to help us understand whether these genes can be used as synergistic targets for immunotherapy.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, COX-2 overexpression mainly improves Treg trafficking into TME. The metabolic interaction between the transformed cells and immune cells also may give rise to the poor response to treatment with ICI, as evidenced by the study of the tumor and immune cell glucose and glutamine metabolism [ 135 ]. In fact, glucose and glutamine metabolism up-regulate the PD-L1 expression in transformed cells by the positive regulation of epidermal growth factor receptor (EGFR)/ extracellular signal-regulated kinase (ERK)/C-Jun pathway [ 135 ].…”
Section: Corresponding Mechanism Complicated In Tumor Resistance To Icismentioning
confidence: 99%
“…The metabolic interaction between the transformed cells and immune cells also may give rise to the poor response to treatment with ICI, as evidenced by the study of the tumor and immune cell glucose and glutamine metabolism [ 135 ]. In fact, glucose and glutamine metabolism up-regulate the PD-L1 expression in transformed cells by the positive regulation of epidermal growth factor receptor (EGFR)/ extracellular signal-regulated kinase (ERK)/C-Jun pathway [ 135 ]. Hence, inhibiting tumor glucose or glutamine metabolism by therapeutic molecules in combination with PD-1/PD-L1 blockade therapies may defeat tumor cell resistance to ICIs.…”
Section: Corresponding Mechanism Complicated In Tumor Resistance To Icismentioning
confidence: 99%